2022
DOI: 10.1038/s41598-022-10126-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dental caries detection with quantitative light-induced fluorescence in comparison to different field of view devices

Abstract: This study evaluated dental caries detection ability between the Qraycam and Qraypen on the same dental caries lesions. A total of 178teeth from 61patients were imaged using Qraypen C®(QC) and Qraycam Pro®(QP) devices and evaluated using analysis software (QA2). Occlusal, secondary, and proximal dental caries were evaluated and scored according to International Caries Detection and Assessment System(ICDAS II) and X-ray criteria. Bland–Altman plots were used to compare quantitative light-induced fluorescence(QL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
(34 reference statements)
0
7
0
1
Order By: Relevance
“…The qualitative light-induced fluorescence (QLF) technique can quantify small alterations in teeth based on autofluorescence, which occurs when the tooth is exposed to 405 nm visible blue light. The QLF device is composed of a light-emitted diode (LED), an inductor filter, and a metal oxide semiconductor sensor [27].…”
Section: Light Fluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…The qualitative light-induced fluorescence (QLF) technique can quantify small alterations in teeth based on autofluorescence, which occurs when the tooth is exposed to 405 nm visible blue light. The QLF device is composed of a light-emitted diode (LED), an inductor filter, and a metal oxide semiconductor sensor [27].…”
Section: Light Fluorescencementioning
confidence: 99%
“…The greater the mineral loss, the greater the loss of tooth fluorescence. Even early lesions with minor mineral changes can be detected and monitored effectively [6,27]. When a lesion exists, an increase in light scattering causes the lesion to appear as dark patches on a bright green background.…”
Section: Light Fluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the comparative reliability of QLF in the detection of primary teeth caries was found to be on par with, or marginally superior to, conventional diagnostic techniques such as visual inspection or radiographic examination under clinical circumstances [66][67][68]. Using QLF technology has proven to be a reliable approach for diagnosing early carious lesions and monitoring the effectiveness of treatment interventions.…”
Section: Fluorescent Techniquesmentioning
confidence: 99%
“…The limitation of these devices is their sensitivity to the external light which impacts the image quality. None of these devices were widely employed in clinical practice [2]. Some investigators focused on the detection of dental caries by OCT. OCT is an infra-red light-based imaging modality that generates cross-sectional images based on the magnitude of backscattered light.…”
mentioning
confidence: 99%